Selection of male goat embryos in vitro by using swim-up of epididymal spermatozoa: Sura Shakir Hammood Al-Dulaimi and Ihsan H. S. Al-Timimi - Al-Timimi, Ihsan H. S. (The Iraqi Journal of Veterinary Medicine, 2018)
The main objectives of this study is the separation of X from Y bearing epididymal spermatozoa of local buck by swim-up, and the use of this spermatozoa for in vitro fertilization to determine the percentage of produced male and female embryos. The sex of produced embryo was identified by polymerase chain reaction. Testis of the local buck were obtained from Al-Shu’alah abattoir and the epididymal spermatozoa were harvested from the cauda by and submitted to in vitro maturation prior to separation of X from Y bearing spermatozoa and prior to their use for in vitro fertilization. For the separation of epididymal spermatozoa, swim-up technique was used with centrifugation at 200×g or 300×g. The centrifugation at 200×g showed that 41.84±1.39 % of spermatozoa were detected in the supernatant while the precipitate contained 50.69±0.71 and the mean of the sperm lost was 7.65±0.93. After centrifugation, spermatozoa in the supernatant were used for in vitro fertilization of matured oocytes. The sex of in vitro produced goat embryos was determined by polymerase chain reaction using specific primers to detect of SRY gene. The percentage of total goat embryos obtained after in vitro fertilization by sperms selected using swim-up at centrifugation force of 200×g recorded 79.66 % male embryos while female embryos recorded only 20.33 %. At the end, the results showed the ability of selection male embryos in caprine by application of swim-up technique on epididymal spermatozoa with centrifugation at 200×g.